The Formation of the Haemostatic Plug – A Special Case of Platelet Aggregation - Lüscher, Ernst F; Weber, Susanne (Thrombosis and Haemostasis, 1993)
The formation of the haemostatic plug is an extremely fast process. This excludes, at least in its first phase, the involvement of soluble activating agents released from or produced by the platelets. An experiment with ADP-activated, formaldehyde-fixed platelets shows that platelets with activated fibrinogen receptors will bind inactive platelets in the presence of fibrinogen and Ca2+-ions. A survey of the literature shows that platelet activation is accompanied by the clustering of the fibrinogen receptors. The surface of an activated platelet, which makes part of the growing haemostatic plug therefore is covered with patches of tightly packed fibrinogen. This allows the multisite combination with the statistically distributed low affinity receptors of the newly arriving platelets. Tightly packed fibrinogen, as present on clusters of the activated GP IIb/IIIa receptors as well as when absorbed to artificial surfaces acts as an activator of platelets. Thus, the propagation of the activation process is possible without a requirement for other, external activators. Such agents, which are released from platelets and, finally, thrombin formation, are nonetheless of vital importance, not for the formation but for the consolidation of the haemostatic plug.